Eye-like ocelloids are built from different endosymbiotically acquired components - Gavelis, Gregory S.; Hayakawa, Shiho; White III, Richard A.; Gojobori, Takashi; Suttle, Curtis A.; Keeling, Patrick J.; Leander, Brian S. (Nature (London), 2015)
Dinoflagellate eye-like ocelloids are built from pre-existing organelles of disparate origin, including a cornea-like layer made of mitochondria and a retinal body made of anastomosing plastids. An eye for phytoplankton The unicellular phytoplankton known as warnowiid dinoflagellates are a prime example of the remarkable diversity which exists in the realm of protsists. Within their single cell, these organisms have complex eyes or 'ocelloids', complete with structures resembling cornea, lens and retina. Gregory Gavelis et al . investigate the evolutionary origin of ocelloids using a single-organelle genomics approach in Erythropsidinium sp., Warnowia sp. and Nematodinium sp. isolates from marine waters off Japan and Canada. They find that ocelloids are built from pre-existing organelles of disparate origin. The cornea is derived from mitochondria, and the retinoid is made of an anastomosing network of plastids, originally derived from a secondary red-algal endosymbiont. Multicellularity is often considered a prerequisite for morphological complexity, as seen in the camera-type eyes found in several groups of animals. A notable exception exists in single-celled eukaryotes called dinoflagellates, some of which have an eye-like ‘ocelloid’ consisting of subcellular analogues to a cornea, lens, iris, and retina 1 . These planktonic cells are uncultivated and rarely encountered in environmental samples, obscuring the function and evolutionary origin of the ocelloid. Here we show, using a combination of electron microscopy, tomography, isolated-organelle genomics, and single-cell genomics, that ocelloids are built from pre-existing organelles, including a cornea-like layer made of mitochondria and a retinal body made of anastomosing plastids. We find that the retinal body forms the central core of a network of peridinin-type plastids, which in dinoflagellates and their relatives originated through an ancient endosymbiosis with a red alga 2 . As such, the ocelloid is a chimaeric structure, incorporating organelles with different endosymbiotic histories. The anatomical complexity of single-celled organisms may be limited by the components available for differentiation, but the ocelloid shows that pre-existing organelles can be assembled into a structure so complex that it was initially mistaken for a multicellular eye 3 . Although mitochondria and plastids are acknowledged chiefly for their metabolic roles, they can also be building blocks for greater structural complexity.